Precarious work : the challenge for labour law in Europe - Kenner, Jeff; Florczak, Izabela; Otto, Marta (Edward Elgar Publishing, 2019)
"Precarious work is a current concern throughout Europe as a result of the proliferation of new types of employment related to the gig economy. This timely book, positioned at the intersection between European and national labour law, provides a comprehensive analysis of the legal and social policy challenges arising from this phenomenon. Since the 2008 financial crisis, there has been an increasing need to respond to the rise of precarious work and the risk it poses to the European model of secure employment and social protection, which this book thoroughly explores. Chapters first consider the theoretical foundations of the issue, before examining the key characteristics and dynamics of employment regulation in Europe related to precarious work, as well as surveying recent judicial decisions. The book demonstrates the potential for improved labour regulation and case law to address the situation both at EU and national level. Precarious Work will prove invaluable to law, politics, sociology and anthropology scholars with an interest in the phenomenon of precarious labour. Lawyers, policymakers and other practitioners working in this area will also find this book a useful resource"--